Economic growth and child poverty reduction in Bangladesh and China - Syeda Shahanara Begum; Deng Quheng; Björn Gustafsson (Institute for the Study of Labor (IZA), 2011)
This paper analyzes child poverty in Bangladesh and China during periods of rapid economic growth in both countries. It compares the extent as well as profile of child poverty in both countries. Comparisons on the extent of child poverty, over time and across countries, are made using a decomposition framework attributing child poverty differences to differences in the three components mean child income, demographic circumstances and the distribution of child income. Child poverty is found to be more extensive in Bangladesh than in China, and is very much a problem for rural children in both countries. The results show that economic growth can reduce child poverty but does not do so always. For understanding changes over time and across countries in the extent of child poverty, it can be necessary to also consider changes/differences in the distribution of child income as well as in the demographic composition.
urn:nbn:de:101:1-20110927577
Keywords: I32; J13; J15; 330; child poverty; economic growth; Bangladesh; China; Kinder; Armut; Wirtschaftswachstum; Einkommensverteilung; Ländlicher Raum; Bangladesch; China